The Genetic Etiology Diagnosis of Fetal Growth Restriction Using Single-Nucleotide Polymorphism-Based Chromosomal Microarray Analysis - Yu'e Chen; Yingjun Xie; Yingjun Xie; Yuying Jiang; Qi Luo; Lijing Shi; Shuhong Zeng; Jianlong Zhuang; Guorong Lyu (Frontiers Media S.A., 2021)
Background: An increase in pathogenic copy number variants (pCNVs) has been recognized to associate with fetal growth restriction (FGR). Here, we aim to explore the application value of chromosomal microarray analysis (CMA) in prenatal diagnosis of FGR.Methods: Prenatal ultrasound was applied to identify FGR. A total of 149 pregnant women with FGR were enrolled in our study. All subjects underwent karyotype analysis and CMA to reveal the chromosomal abnormalities.Results: In this study, all subjects were successfully detected by karyotype and CMA analyses. Of these subjects, the chromosomal abnormalities detection rate was 5.37% (8/149) for karyotyping and 13.42% (20/149) for CMA, respectively. Among them, an 8.05% (12/149) incremental yield of CMA over karyotype analysis was observed (p = 0.004). In addition, a significant difference of pCNV detection rate was observed between the groups with different high-risk factors (p = 0.005). The FGR with structural anomalies group showed the highest pCNV detection rate (33.33%), followed by the FGR with non-structural anomalies group (8.77%) and the isolated FGR group (8.06%).Conclusion: In conclusion, CMA technology showed an effective application value in etiology diagnosis of FGR. We believe that CMA should be recommended as first-line detection technology for prenatal diagnosis in FGR.